A Case Report of Loperamide-Induced Ventricular Storm - Jerome De Vera DO; Hyungjin Ben Kim DO; Antoine E. Sakr MD (SAGE Publishing, 2021)
Loperamide is an easily accessible antidiarrheal medication. Unlike other medications in its class, loperamide is unique in that it causes euphoria at supratherapeutic levels due to its effect on opioid receptors. Unfortunately, with its growing abuse potential also comes increasing reports of cardiotoxicity including prolonged QT, torsades de pointes, and sudden cardiac death. We report a case of a 29-year-old female who presented with unstable arrhythmia that further progressed into electrical storm in the setting of loperamide toxicity. Due to its growing popularity and availability, it is important for clinicians to understand loperamide's mechanisms for causing toxicity as well as how to appropriately treat its complications.